Comunicação química em quelônios dulcícolas: reconhecimento específico e possíveis impactos de uma espécie invasora - Silva, Roberta Mariáh Teodósio (2020)
Although chemical communication is widely used by turtles for various social and sexual behaviors, few studies address freshwater turtles. Chemical communication between different species of turtles is also an area to be explored. The introduction of exotic species is a major threat to turtles; however, the impact of chemical cues from invasive species on native Brazilian species is still unknown. We hypothesized that the focal native species were able to recognize the chemical cues of their own species and of the invasive species and that the presence of the exotic chemical cue would affect the use of space by the native species. For this purpose, the influence of chemical cues from the invasive exotic species (Trachemys scripta elegans) on the choice of aquatic environments and thermoregulation sites by species of native freshwater turtles was tested experimentally. A first experiment investigated the influence of the chemical cues of the invasive species on the choice of aquatic environments by the black-bellied slider (Trachemys dorbigni). The animals were individually subjected to binary choice tests in which they could choose between two water samples with treatments varying between clean water, water with chemical cues of conspecifics and water with chemical cues of the invasive species. In the second experiment, it was investigated the effect of chemical cues on the choice of thermoregulation sites by the giant South American river turtle (Podocnemis expansa) and yellow-spotted Amazon River turtle (Podocnemis unifilis). In an open enclosure containing the native animals, wooden structures were available with three treatments (with chemical cues of the subject species, with chemical cues of the invasive species or with no chemical cues) and the use of the structures by the subject animals was observed. The tested black-bellied sliders demonstrated to differentiate the chemical cues of their own species from the chemical cues of the invasive species, since when these two water samples were contrasted there was a significant preference of T. dorbigni females for water samples with chemical cues of conspecifics. However, when the water samples with chemical cues were contrasted with clean water, the animals did not prefer any sample. The species P. expansa and P. unifilis showed no differences in the frequency of use of the thermoregulation sites in relation to the treatments offered. Although it was not possible to establish a clear relationship between the presence of the chemical clue of the invasive species in the environment and the use of space by the tested native species, this study constitutes an important step in the study of the chemical ecology of freshwater turtles and its implications for conservation of native species in Brazil.